Chemoselective Preparation of 1, 1-Diacetates from Aldehydes, Mediated by a Keggin Heteropolyacid Under Solvent Free Conditions at Room Temperature. Issue 1 (2007) - Romanelli, G.; Dimitroff, P.; Vázquez, P.; Autino, J. C.
Abstract : A simple, general and efficient method has been developed for the conversion of aldehydes to 1, 1-diacetates using acetic anhydride, a catalytic amount of non commercial Keggin heteropolyacid (H6 PalMo11 O40 ) (1% mol) in solvent free conditions at room temperature. Aromatic and aliphatic, simple and conjugated aldehydes were protected with excellent yields.